Peradilan Tindak Pidana Korupsi Bagi Anggota Militer - Kadek Wijana; I Made Sepud; Anak Agung Sagung Laksmi Dewi (Fakultas Hukum Universitas Warmadewa, 2020)
Abstract—The military is the one who is educated, trained and prepared for battle. Citizens of Indonesia who was inducted into the military in carrying out his duties in addition to obey pancasila values, sapta marga and the soldier's oath is required always to be obedient and submissive to all the legal rules that apply specifically to Members Of The Military. Members of the military who are proven violation of the law including criminal acts of corruption should be dealt with in accordance with the applicable law. As for the formulation of the problem (1) how is the examination of the criminal acts of Corruption committed by members of the military? (2) How did the authorities prosecute criminal acts of Corruption against members of the military? This research used the methods of normative, approach in legislation, the conceptual approach, the primary legal materials, legal materials, legal materials tertiary secondary, the study documents, studies, studies of internet libraries as well as the analysis of interpretation of law and descriptive analysis. Court martial proceedings are actually the same with public justice, but the term for the Prosecutor and investigators are generally different. In finding of the judiciary which is used to handle the matter, the connections can be seen from losses resulting from such criminal deeds. Judges in condemning military members who commit criminal acts of corruption should be the same as the perpetrator of the criminal offence of corruption court.